Central African Republic : Request for a Staff Monitored Program. (IMF Staff Country Reports; Country Report ;, 2022)
President Touadera was reelected for a second term, despite attempts by armed groups to prevent the general and presidential elections from being held. While the security situation has improved since these groups' attacks on Bangui were repulsed in January, the prolonged closure of the trade corridor with Cameroon had a substantial economic and fiscal impact, significantly affecting the growth prospects for this year and the cash position of the government. The government's relations with development partners have deteriorated causing delays in grants disbursements. The number of Covid-19 cases and deaths temporarily increased in the Spring but has returned to a very low level. The three-year ECF arrangement approved in December 2019 is off track, with most performance criteria and structural benchmarks missed prior to the intensification of the domestic conflict, and the third review has not been completed.